The Role of Mythological Narratives in Shaping Gender and Identity in Girish Karnad’s Drama - Rani, Monika; Kumar, Suresh (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In this paper, attention is paid to the way Girish Karnad creatively applied the legendary tales to contemporary Indian theater in order to explore gender, identity, and social systems that are highly complex. Karnad is a reinterpretation of ancient narratives in the Mahabharata, the Puranas, and the local mythology and transforms it into a helpful aid to the investigation of gender roles and relations in the modern society. The paper demonstrates that Karnad plays such as Yayati (1961), Hayavadana (1972), Nagamandala (1988), and The Fire and the Rain (1998), break the gender roles, provide women with a greater power, and help them to doubt what society expects them to be. It is done using a qualitative and interpretive approach that relies on close textual analysis, postcolonial feminism, and archetypal criticism and is applied to carry out detailed readings of dialogues, actions of characters, and symbols. These are next outlined against their mythological backgrounds to indicate how Karnad modernizes and censures these myths. The paper also examines how the identity, desire and freedom in the Indian society and culture following independence are reflected through the storytelling, pictures and symbolic themes such as the snake in Nagamandala or the fire in The Fire and the Rain. The findings indicate that the stage versions of the stories that Karnad does are not wholly respectful as well as not dismissive. Rather, they form a shifting medium in which gender relationships, psychological depth and social commentary converge. This study highlights the role of Karnad in relating the custom and modernity, this paper demonstrates how myths can be applied to interpret identity, power of women, and share of power in contemporary society.